Implementation of Qur'anic Values in Educating Children (Interpretation of Surah Luqman Verses 13, 14, 16, 18, and 19) - Safaat, Ahmad Wafi Nur (Jurnal Indonesia Sosial Sains, 2025)
The phenomenon of moral crisis among Indonesian children and adolescents indicates a weakness in character education, especially in the family environment. Education that emphasizes academic aspects too much without instilling spiritual and moral values impacts the fading of children's manners and behavior. In fact, Islam, through the Qur'an, provides in-depth guidelines on how to educate children, one of which is through the story of Luqman's advice to his son. This research aims to examine and explore the values of education in Surah Luqman verses 13, 14, 16, 18, and 19 as a conceptual basis for shaping the character of children who are monotheistic, moral, and responsible. This study uses a qualitative method with a literature study approach. Data were collected from classical and contemporary tafsir books as well as scientific journals from Google Scholar and Neliti. The results of the study show that Luqman's advice includes five main values, namely monotheism, birrul walidain, awareness of Allah's supervision, humility, and social manners. These values form an integrative and applicable educational framework to be applied in today's Muslim families. By understanding and applying these values, parents are expected to be able to form a strong generation in morals and spirituality.